2019
DOI: 10.3390/ma12060958
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanopillar Crystalline ITO Thin Films with High Transmittance and IR Reflectance by RF Magnetron Sputtering

Abstract: Nanopillar crystalline indium tin oxide (ITO) thin films were deposited on soda-lime glass substrates by radio frequency (RF) magnetron sputtering under the power levels of 100 W, 150 W, 200 W and 250 W. The preparation process of thin films is divided into two steps, firstly, sputtering a very thin and granular crystalline film at the bottom, and then sputtering a nanopillar crystalline film above the bottom film. The structure, morphology, optical and electrical properties of the nanopillar crystalline ITO t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…TCOs have attracted lots of attention because they show simultaneously conductivity and optical transparency. In the past fifty years, indium tin oxide (ITO) has become the most widely used TCO for optoelectronic devices due to its high transmittance of~90% in the visible range and low resistivity (~2 × 10 −4 Ω-cm) with mobility of about 40 cm 2 /Vs and high carrier concentration of 10 21 cm −3 [8,9]. However, ITO faces several challenges.…”
Section: Introductionmentioning
confidence: 99%
“…TCOs have attracted lots of attention because they show simultaneously conductivity and optical transparency. In the past fifty years, indium tin oxide (ITO) has become the most widely used TCO for optoelectronic devices due to its high transmittance of~90% in the visible range and low resistivity (~2 × 10 −4 Ω-cm) with mobility of about 40 cm 2 /Vs and high carrier concentration of 10 21 cm −3 [8,9]. However, ITO faces several challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a highest diffraction peak (222) of the ITO film is observed, which indicates that it is preferentially oriented in the <111> plane. Several research groups have reported that the (222) diffraction peak and (400) diffraction peak, the <100> plane, are related to the oxygen content [10][11][12]. They point out that the <111> plane can accommodate more oxygen atoms, while the <100> plane can accommodate more oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it shows completely different surface properties from sputtered ITO grown in multistructured nanopillar crystals; ITO NPs show different surface and cross-sectional morphologies by agglomeration of nanoparticles after heat treatment. 34 In general, the high optical transmittance of a thin film is mainly related to smooth surface roughness, small crystal size, good uniformity, and low refractive index. 45 In particular, an increase in crystallinity due to an external energy source greatly affects the optical and electrical properties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, our group has also studied various materials, such as the AgNW network, self-assembled network, W-doped In 2 O 3 , and MoO 3 –Ag–MoO 3 . Despite the high electrical and thermal conductivities of AgNW, AgNW-based transparent conductors are easily oxidized in air, have low heat and oxidation resistance, and have a rough surface. , Furthermore, TFH electrode materials were studied through a large-area roll-to-roll process with CuO x –Cu–CuO x , InZnSiO–Ag–InZnSiO, ZnSnO–AgPdCu–ZnSnO, ITO–Cu–ITO, and ITO–Ag–ITO. Although nanoparticle-based oxide electrode such, as InZnO, InZnSnO, InTiO, and InSnO has been reported, research into solution-based ITO conductors and solution-multilayers for transparent TFHs is still insufficient. Specifically, studies on the crystallinity, preferred orientation, and electrical and optical properties depending on the thickness of the sputtered ITO have been conducted; however, for the outstanding electrical and optical properties of ITO NPs, studies on optimizing the thickness and annealing process have not been sufficiently performed. It suggests that ITO NPs, which do not require vacuum conditions, can be the starting point for research on cost-effective all-solution electronic devices. , In this work, we studied a cost-effective ITO NP solution-based electrode for high-performance TFHs.…”
Section: Introductionmentioning
confidence: 99%